2018
DOI: 10.1038/cmi.2017.163
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and allergic role of IL-33-induced neutrophil polarization

Abstract: Neutrophils are involved in the pathogenesis of allergy. However, the contribution of the different functionally polarized neutrophils in allergy needs to be clarified. We sought to define the characteristics of interleukin (IL)-33-induced neutrophils and the involvement of this subset of polarized neutrophils in allergic pathogenesis. Freshly isolated neutrophils were treated with different cytokines and the cytokine expression levels were detected by real-time PCR. The gene expression profile of IL-33-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 54 publications
0
46
0
Order By: Relevance
“…In addition, a very recent study showed that IL-33 induces neutrophil polarization to selectively produce Th2-type cytokines, which might also contribute to pathological changes in asthma. 24 It is also of great interest that, in the present study, per-nasal airway administration of IL-25 and IL-33 induced the accumulation of ILC2s not only in the lung parenchyma, airway lumen and mediastinal lymph nodes but also, at least transiently, in the spleen, thymus and bone marrow of the challenged animals. A recent study also showed that IL-25 and IL-33 administered into the peritoneal cavity of mice increased the number of ILC2s in the lung.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In addition, a very recent study showed that IL-33 induces neutrophil polarization to selectively produce Th2-type cytokines, which might also contribute to pathological changes in asthma. 24 It is also of great interest that, in the present study, per-nasal airway administration of IL-25 and IL-33 induced the accumulation of ILC2s not only in the lung parenchyma, airway lumen and mediastinal lymph nodes but also, at least transiently, in the spleen, thymus and bone marrow of the challenged animals. A recent study also showed that IL-25 and IL-33 administered into the peritoneal cavity of mice increased the number of ILC2s in the lung.…”
Section: Discussionmentioning
confidence: 49%
“…Effects of IL-33 or CXCL16 on the activation of the ERK, p38, JNK, Akt, and NF-κB pathways in ILC2s IL-33 binds to ST2 and initiates the recruitment of Mal or MyD88 signaling adaptor molecules, leading to the activation of downstream pathways (including NF-κB and MAPKs). 23,24 In murine peritoneal macrophages, human aortic smooth muscle cells and human umbilical vein endothelial cells, CXCL16 activated ERK1/2, p38, and PI3K/Akt, respectively. 21,25,26 To determine whether IL-33 or CXCL16 can activate these signaling pathways in ILC2s, we treated ILC2s with IL-33 (60 ng/ml) or CXCL16 (10 ng/ ml) (the optimal concentrations of IL-33 and CXCL16 in vitro in the transwell assay) for 10 min.…”
Section: Il-33 and Cxcl16 Induced Ilc2 Chemotaxis In Vitromentioning
confidence: 99%
“…Western blot analysis was performed on total proteins extracted from samples as previously described. 71 Proteins were harvested by lysing collected cells with 200 ml of RIPA buffer containing protease inhibitor and phosphatase inhibitor cocktail tablets (Roche, Brussels, Belgium). Western blotting was performed using standard procedures with the following primary antibodies: c-FOS (9F6) rabbit mAb (catalog number 2250), c-JUN (60A8) rabbit mAb (catalog number 9165), phosphor-c-FOS (Ser32) rabbit mAb (D82C112), phosphor-c-JUN (Ser73) rabbit mAb (D47G9), NFκB p65 (L8F6) mouse mAb (catalog number 6596), phosphor-NFκB p65 (Ser468) (catalog number 3039), and β-Actin (13E5) rabbit mAb (catalog number 4970) used as a loading control from Cell Signaling Technology (Leiden, The Netherlands); ACSL3 (sc-166374) from Santa Cruz; and IκBA (ab32518), Bax (ab32503), Hexokinase 1 (ab150423), Chk1 (ab32531), PFKP (ab204131), ERK1/ 2 (ab184699), and p-ERK1/2 (ab201015) from Abcam (China).…”
Section: Western Blottingmentioning
confidence: 99%
“…Different subsets of T cells (including CD4 + , CD8 + , γδ, and dendritic epidermal T cells, or DETCs), mast cells, basophils, type 2 innate lymphoid (ILC2) cells, eosinophils, natural killer (NK) cells, natural killer T (NKT) cells, monocytes, and neutrophils have been shown to express IL‐4 and/or IL‐13 during allergic inflammation (Bao & Reinhardt, 2015; Chen et al., 2014; Sun et al., 2018; Vantourout & Hayday, 2013; von Bubnoff et al., 2010). To address whether these and other cell types express IL‐4 or IL‐13 in the skin after MC903 treatment, we wanted to quantify these cell subsets and various macrophage subpopulations, as they are known to be responsive to type 2 cytokines.…”
Section: Commentarymentioning
confidence: 99%